Conversion of Rutin, a Prevalent Dietary Flavonol, by the Human Gut Microbiota - Riva, Alessandra; Kolimár, Ditta; Spittler, Andreas; Wisgrill, Lukas; Herbold, Craig W.; Abrankó, László; Berry, David (Frontiers in Microbiology, 2020)
The gut microbiota plays a pivotal role in the conversion of dietary flavonoids, which can affect their bioavailability and bioactivity and thereby their health-promoting properties. The ability of flavonoids to stimulate the activity of the microbiota has, however, not been systematically evaluated. In the present study, we used a fluorescence-based single-cell activity measure [biorthogonal non-canonical ammino acid-tagging (BONCAT)] combined with fluorescence-activated cell-sorting (FACS) to determine which microorganisms are stimulated by the flavonoid rutin. We performed anaerobic incubations of human fecal microbiota amended with rutin and in the presence of the cellular activity marker L-Azidohomoalanine (AHA) to detect rutin-stimulated cells. We found that 7% of cells in the gut microbiota were active after a 6 h incubation and 23% after 24 h. We then sorted BONCAT-positive cells and observed an enrichment of Lachnospiraceae (Lachnoclostridium, and Eisenbergiella), Enterobacteriaceae, Tannerellaceae and Erysipelotrichaceae species in the rutin-responsive fraction of the microbiota. There was marked inter-individual variability in the appearance of rutin conversion products after incubation with rutin. Consistent with this, there was substantial variability in the abundance of rutin-responsive microbiota among different individuals. Specifically, we observed that Enterobacteriaceae were associated with conversion of rutin into quercetin-3-glucoside and Lachnospiraceae were associated with quercetin production. This suggests that individual microbiotas differ in their ability to metabolize rutin and utilize different conversion pathways.